Pengaruh Marinasi Ekstrak Jahe (Zingiber Officinale)Terhadap Kualitas Fisik Daging Ayam Afkir: The Effectiveness of Giving Ginger Extract to The Physical Quality of Laying Chicken Meat - Andi Parunrungi; Andi Mutmainna; Irmawaty Majid; Aminah Hajah Thaha (Universitas Islam Negeri Alauddin Makassar, 2023)
Improving the quality of the meat so that it is tender before boiling the meat with the meat marination treatment. The marination process can be utilized using vegetable ingredients that contain protease enzymes such as ginger extract. This study aims to determine the effect of soaking ginger juice on the pHysical quality of rejected laying hens. This study used aged ginger and discarded layer chicken meat at the age of 2 years. The research method used was a Completely Randomized Design (CRD) with 4 treatments and 4 replications. With treatment P0 = Without soaking ginger juice (Control), P1 = 50g rejected chicken meat + 50 ml ginger juice + 15 minutes soaking time, P2 = 50g rejected chicken meat + 50 ml ginger juice + 30 minutes soaking time, P3 = Chicken meat rejected 50g + ginger juice 50 ml + soaking time 45 minutes. Data analysis used Analysis of Variance (ANOVA). Based on the results of the variance, it gave unrealistic results (P>0.05) on pH, water holding capacity, cooking loss and breaking power of meat. Soaking The Ginger Extract for 15 minutes is able to provide maximum results in improving the physical quality of rejected laying hens.